Some physical properties of K2TlAsX6 (X = Cl, Br) and CsPbBr3 semiconducting compounds - Bioud, Nadhira (International Journal of Advanced Chemistry, 2024)
Some physical properties of K2TlAsX6 (X = Cl, Br) double perovskite compounds have been predicted using the theoretical unit cell parameters and elastic constants computed by Munir et al. (Materials Science and Engineering B 298 (2023) 116830). At equilibrium the Debye temperatures of K2TlAsCl6 and K2TlAsBr6 materials were found to be 193.5 K and 159.6 K, respectively. Furthermore, the mass density, the longitudinal, transverse and mean acoustic wave speeds, the acoustic impedance and the Debye temperature of Cesium Lead Bromide (CsPbBr3) inorganic perovskite compound under high stress up to 15 GPa have been predicted using the theoretical unit cell parameters and elastic constants computed by Junaid Zaidi et al. (Materials Research Express, Vol. 9, No. 12, (2022) 125501). To the best of our knowledge, there is no any data in the literature that can be compared to the findings we’ve achieved on the Debye temperature of K2TlAsX6 (X = Cl, Br) and CsPbBr3 materials.